Evaluation of patients with negative PCR tests after COVID-19 pneumonia in intermediate-level intensive care unit - Ata, Filiz; Yılmaz, Canan; Karaca, Ümran; Özyaprak, Buket; Balkaya, Ayşe Neslihan; Aytünür, Cihan Sedat; Onur, Tuğba (The European Research Journal, 2023)
Objectives: The need for an intensive care unit has increased during the pandemic of coronavirus disease (COVID-19). For this reason, intermediate-level intensive care units (IICUs) were established in hospitals worldwide. This study aims to evaluate the data of patients that hospitalized in IICU. Methods: Patients under treatment for COVID-19 were followed up in IICU after the negative polymerized chain reaction test. A total of 52 patients were evaluated retrospectively between August 24, 2020 and March 1, 2021. The patients were divided into two groups according to discharge status from IICU (Group 1: exitus, Group 2: transferred to clinic, or discharged home). Demographic data, comorbidities, Acute Physiology and Chronic Health Evaluation II (APACHE II), Glasgow Coma Scale (GCS), treatments and procedures, and complications were recorded. Results: Seventeen (32.7%) of 52 patients who were followed up in IICU died. Thirty-five patients (67.3%) were transferred to the clinic or discharged home. The APACHE II scores at admission to IICU were higher in Group 1 (26.11 ± 5.86) than in Group 2 (23.43 ± 6.32) but not statistically significant. GCS was statistically significantly lower in Group 1 than in Group 2 (7.82 ± 2.42 and 10.25 ± 2.58, respectively, p = 0.002). Mechanical ventilation rate (82.3%) and the need for inotropic agents (76.5%) were higher in Group 1 (p = 0,034 and p < 0.001, respectively). Tracheostomy was applied to 5 of all patients, and percutaneous endoscopic gastrostomy was performed 4 of them. Conclusions: We think that IICU created during the pandemic provides effective treatment for patients needing intensive care. We think IICU is beneficial in providing quick patient discharge in tertiary intensive care units.